2020
DOI: 10.3390/cryst10060431
|View full text |Cite
|
Sign up to set email alerts
|

Electromechanically Rotatable Cross-Shaped Mid-IR Metamaterial

Abstract: We present an electromechanically rotatable infrared (IR) cross-shaped metamaterial (CSM) in the mid-IR wavelength range. The CSM configuration is composed of double gold layers with cross-shaped nanostructures. To investigate the fano-resonance within CSM nanostructures, the aspect ratios and length ratios of CSM are compared and discussed. The electromagnetic responses exhibit the characteristics of large tuning range, tunable broad and narrow bandwidths. By properly tailoring the aspect ratio of CSM, the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…They are widely studied to realize thermal emitters and are perfect absorbers for energy harvesting, medical imaging, and high-sensitivity sensing applications [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. By tailoring the geometrical dimensions, metamaterials can be designed to span broad operating wavelengths, including visible [ 31 , 32 , 33 ], IR [ 34 , 35 , 36 , 37 , 38 , 39 ], terahertz [ 40 , 41 , 42 , 43 , 44 ], and microwave light [ 45 , 46 ]. To provide metamaterials with more flexibility, there are many techniques proposed for tuning mechanisms using MEMS technology [ 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ]: liquid crystal [ 55 ], photo-excited [ 56 ], phase-change materials [ 57 , 58 ], thermal annealing [ …”
Section: Introductionmentioning
confidence: 99%
“…They are widely studied to realize thermal emitters and are perfect absorbers for energy harvesting, medical imaging, and high-sensitivity sensing applications [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. By tailoring the geometrical dimensions, metamaterials can be designed to span broad operating wavelengths, including visible [ 31 , 32 , 33 ], IR [ 34 , 35 , 36 , 37 , 38 , 39 ], terahertz [ 40 , 41 , 42 , 43 , 44 ], and microwave light [ 45 , 46 ]. To provide metamaterials with more flexibility, there are many techniques proposed for tuning mechanisms using MEMS technology [ 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ]: liquid crystal [ 55 ], photo-excited [ 56 ], phase-change materials [ 57 , 58 ], thermal annealing [ …”
Section: Introductionmentioning
confidence: 99%
“…In view of tunable metamaterial absorber is indispensable to perform the controllable modulator, flexible photovoltaic device, and tunable sensor, [ 26–29 ] it becomes a research hot topic recently. The tuning mechanisms of tunable metamaterial absorbers are included but not limited to the uses of a phase change material, [ 30 ] electrical control, [ 31,32 ] liquid crystal, [ 33,34 ] and micro‐electro‐mechanical system (MEMS) technique [ 35–42 ] to dynamically tune the absorption resonance. To actively achieve the control of absorption spectrum, these tuning methods are limited to only certain electromagnetic property, which is either resonant frequency or resonant intensity.…”
Section: Introductionmentioning
confidence: 99%
“…There has been much research presenting and demonstrating the use of diversified SRR designs [8][9][10][11][12][13], either symmetrically or asymmetrically, such as cross-shaped SRR [9], V-shaped SRR [10,11], spiral-shaped SRR [12], and multiple SRRs [13]. In view of these extraordinary optical properties of SRR-based metamaterials, there have been extensive studies reported in the different frequency ranges, from microwave, terahertz (THz), and infrared to visible spectra [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%